EKSPERIMENTASI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT DAN NUMBERED HEADS TOGETHERDENGAN PENDEKATAN MATEMATIKA REALISTIK PADA MATERI LUAS PERMUKAAN BANGUN RUANG DITINJAU DARI KEAKTIFAN BELAJAR - Komsatun, Siti; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT: The purpose of this research was to determine the effect of learning models with approach on achievement of mathematics viewed from the student active learning. The learning approach compared were Teams Games Tournament with Realistic Mathematics Education (RME) approach, Numbered Heads Together (NHT) with Realistic Mathematics Education (RME) approach, and direct learning. This research was a quasi-experimental research with 3x3 factorial design. The population was all of the 2nd grade students of junior high school in Klaten regency. Sampling was done by stratified cluster random technique. The instruments used to collect data were the prior mathematics knowledge test, activity learning questionnaire, and achievement of mathematics test. The hypothesis test used unbalanced two way anova. The hypothesis test concluded that (1) students who taughtÂ  by TGT learning model with RME approach had the same learning achievement of students who taught NHT models with RME approach, students who taughtby TGT model with RME approach have better achievements mathematics learning than students who taught by direct learning, students who taught by NHT models with RME approach mathematics learning achievement better than students who taught by direct learning (2) based onthe results of unbalanced two way anova in each active category (high, medium, low), havenâtÂ  the same learning achievement if taught TGT-RME learning models, NHT-RME, or directly, but based on the results of post hoc test anova have the same in the academic achievement of each activity category (high, medium, low) if taught TGT-RME learning model, NHT-RME, or directly. (3) based on the results of unbalanced two way anova havenât the same in mathematics achievement in each category learning model(TGT-RME, NHT-RME, direct), between students with high active, medium, or low. However, based on post hoc anova, in each category learning model (TGT-RME, NHT-RME, right), students with high active, medium, or low have the same of mathematics achievement. Keywords: TGT-RME, RME-NHT, active student learning, mathematics learning achievements